Pharmacokinetic Interactions of Clinical Interest Between Direct Oral Anticoagulants and Antiepileptic Drugs - Galgani, Alessandro; Palleria, Caterina; Iannone, Luigi Francesco; De Sarro, Giovambattista; Giorgi, Filippo Sean; Maschio, Marta; Russo, Emilio (Frontiers in Neurology, 2018)
Direct oral anticoagulants (DOACs), namely apixaban, dabigatran, edoxaban and rivaroxaban, are being increasingly prescribed among the general population, as they are considered to be associated to lower bleeding risk than classical anticoagulants, and do not require coagulation monitoring. Likewise, DOACs are increasingly concomitantly prescribed in patients with epilepsy taking, therefore, antiepileptic drugs (AEDs), above all among the elderly. As a result, potential interactions may cause an increased risk of DOAC-related bleeding or a reduced antithrombotic efficacy. The objective of the present review is to describe the pharmacokinetic interactions between AEDs and DOACs of clinical relevance. We observed that there are only few clinical reports in which such interactions have been described in patients. More data are available on the pharmacokinetics of both drugs classes which allow speculating on their potential interactions. Older AEDs, acting on cytochrome P450 isoenzymes, and especially on CYP3A4, such as phenobarbital, phenytoin and carbamazepine, are more likely to significantly reduce the anticoagulant effect of DOACs (especially rivaroxaban, apixaban and edoxaban). Newer AEDs not affecting significantly CYP or P-gp, such as lamotrigine or pregabalin, are not likely to affect DOACs efficacy. Zonisamide and lacosamide, which do not affect significantly CYP activity in vitro, might have a quite safe profile, even though their effects on P-gp are not well known, yet. Levetiracetam exerts only a potential effect on P-gp activity, and thus it might be safe, as well. In conclusion, there are only few case reports and limited evidence on interactions between DOACs and AEDs in patients. However, the overall evidence suggests that the interaction between these drug classes might be of high clinical relevance and therefore further studies in larger patients’ cohorts are warranted for the future in order to better clarify their pharmacokinetic and define the most appropriate clinical behavior.